(untitled) (Balneo and PRM Research Journal, 2024)
Abstract: Treatment for chronic rheumatic diseases, included various modalities for pain management and for functioning modulation, has the main gole to increase the quality of life and to improve also the activities of daily living. Seronegative spondyloarthropathies (SpA) are a group of rheumatologic disorders that include ankylosing spondylitis, psoriatic arthritis, entheropatic SpA, reactive arthritis and undifferentiated SpA. Treatment methods include clasically pharmacological modalities. Physical therapy should also be highlighted as being part of the treatment. Balneotherapy and spa therapy are increasingly taken into account in evidence-based treatment guidelines for multiple rheumatic diseases, for specific effects on functional parameters and also for the involvement in cartilage regeneration. Balneotherapy is universally defined as the treatment method which uses bathing in thermal and mineral waters. Other balneological treatments include peloidotherapy, balneological gases and therapeutic waters in various forms of bathing, inhalation or drinking. Spa therapy comprises complementary and alternative treatment modalities including balneotherapy, hydrotherapy, exercises, and massage therapy. This systematic literature review aims to highlight the effects of balneotherapy in spondylarthropathies. The review is based on the internationally accepted method, the “PRISMA” methodology- “Preferred Reporting Items for Systematic Reviews and Meta-Analysis”. Keywords: balneotherapy; spondylarthropathies; regeneration; articular cartilage.